HUBUNGAN EFIKASI DIRI DAN INTERAKSI SOSIAL DENGAN PRESTASI BELAJAR PADA MAHASISWA JURUSAN BIMBINGAN KONSELING ISLAM FAKULTAS DAKWAH DAN ILMU KOMUNIKASI IAIN PADANGSIDIMPUAN - LIS YULIANTI SYAFRIDA SIREGAR (Tazkir: Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2015)
The research aims to know relation, (1) self-efficacy and achievement  of study, (2) social interaction and achievement of study, (3) with together between self-efficacy and social interactionwith achieviement of study in student environment guidance conceling Islamic Department Dawah Faculty and Communication science of IAIN Padangsidimpuan on academic 2013/2014. Kind of this research expost facto. Population of the research all of students guidance conceling Islamic Department Dawah Faculty and Communication science of IAIN Padangsidimpuan on academic 2013/2014, are totally 187 students sampling technique is used sampling nonprobability with saturate sample technique on often mentioned study cencus so sample totally 187 students.Collecting data method is used that questionarry method to measure self-efficacy and social interaction and record keeping method to measure of achievement study. Analysis data technique is used descriptive statistic analysis and regression analysis.The results showed that: (1) (1) there is a positive and significant relationship between self-efficacy and the learning achievement with a correlation of 0.686. (2) There is a positive and significant relationship between interaction social and the learning achievement with a correlation of 0.788. (3) Taken together there is a positive and significant relationship between self-efficacy and interaction social to learning achievement with correlation of 0.854. Based on these results, it was concluded that student achievement is influenced by self-efficacy and interaction social.